2020
DOI: 10.1002/cyto.b.21939
|View full text |Cite
|
Sign up to set email alerts
|

Eleven‐marker 10‐color flow cytometric assessment of measurable residual disease for T‐cell acute lymphoblastic leukemia using an approach of exclusion

Abstract: Measurable/minimal residual disease (MRD) status has been suggested as a powerful indicator of clinical-outcome in T-cell lymphoblastic leukemia/lymphoma (T-ALL). Multicolor flow cytometric (MFC)-based T-ALL MRD reports are limited and traditionally based on the utilization of markers-of-immaturity like TdT and CD99. Moreover, studies demonstrating the multicolor flow cytometric (MFC) approach for the assessment of T-ALL MRD are sparse. Herein, we describe an 11-marker, 10-color MFC-based T-ALL MRD method usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 50 publications
(129 reference statements)
5
32
1
Order By: Relevance
“…It is simpler, faster, less expensive and broader than PCR‐based methods. In our present study, the percentage of detectable FCM‐MRD was 96·9%, consistent with reported rates of 93%, 98% and 100% in patients with T‐ALL 17,21,22 . In addition, it should be noted that our present cohort included some ETP patients and these patients usually lack sensitive PCR markers, 17,23 further emphasising the need for FCM‐MRD monitoring of these patients.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…It is simpler, faster, less expensive and broader than PCR‐based methods. In our present study, the percentage of detectable FCM‐MRD was 96·9%, consistent with reported rates of 93%, 98% and 100% in patients with T‐ALL 17,21,22 . In addition, it should be noted that our present cohort included some ETP patients and these patients usually lack sensitive PCR markers, 17,23 further emphasising the need for FCM‐MRD monitoring of these patients.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, they used two‐colour FCM to determine MRD at the time, which was less sensitive and specific than our present six‐ to eight‐colour FCM technology 14 . The relapse rate of our present cohort was higher than that in some previous reports, especially in children 17,22 . Differences in population characteristics and treatment protocols might explain these discrepancies.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations